1996
DOI: 10.1063/1.116173
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen containing hydrogenated amorphous carbon for thin-film field emission cathodes

Abstract: Field emission measurements using 0.3 m thick nitrogen containing hydrogenated amorphous carbon films ͑a-C:H:N͒ on n ϩϩ -Si cathodes are reported. Onset emission fields as low as 4 V m Ϫ1 have been obtained using a flat plate anode configuration. Uniform emission is observed over the entire cathode area at current densities below 7ϫ10 Ϫ2 mA cm Ϫ2 . At higher current density preferential emission from spots is observed. The spot emission is imaged using the ITO coated plate anode. A model based on the a-C:H:N a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
214
3
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 481 publications
(222 citation statements)
references
References 11 publications
4
214
3
1
Order By: Relevance
“…However, in both of these types of films there has been a reduction in the spin density and this was partly attributed to passivation of defects. [4,17] It can be seen from Fig. 3 (a) that E th drops with addition of N similar to that reported elsewhere [4,16] but in contrast to the DLC films of Silva et al, [18] no reduction in N s is observed (Fig 3 (b)).…”
Section: (A)mentioning
confidence: 44%
See 3 more Smart Citations
“…However, in both of these types of films there has been a reduction in the spin density and this was partly attributed to passivation of defects. [4,17] It can be seen from Fig. 3 (a) that E th drops with addition of N similar to that reported elsewhere [4,16] but in contrast to the DLC films of Silva et al, [18] no reduction in N s is observed (Fig 3 (b)).…”
Section: (A)mentioning
confidence: 44%
“…In order to demonstrate that it is the size of the cluster that is still important in determining the emission mechanism rather than the absolute concentration of the clusters we have made measurements of the threshold field and spin density as a function of N content in the low defect polymeric films. Addition of N has been shown previously to reduce the threshold field in diamond-like carbon (DLC) films [4] and also in ta-C films [17]. However, in both of these types of films there has been a reduction in the spin density and this was partly attributed to passivation of defects.…”
Section: (A)mentioning
confidence: 88%
See 2 more Smart Citations
“…[17] In this model the a-C film acts as an interlayer with the true cathode being the underlying Si or metal substrate, with the crucial factor being the heterojunction that formed at the back contact. [18] In the case of DLC and ta-C films the density [16] of unpaired electron states near to the Fermi level is higher (10 20 cm -3 ). These films have a high sp 2 content as well as a large band gap (>2 eV) and as a consequence the wavefunction overlap of the clusters will result in electron delocalization [19] and/or enhanced hopping between the clusters that will enhance the connectivity, as shown in Fig.…”
Section: Field Emission From Carbon Based Materials and Criteria For mentioning
confidence: 99%